Pengaruh Pendidikan Kesehatan dengan Media Gamifikasi Berbasis Website Genially terhadap Tingkat dan Pengelolaan Stres Kerja pada Guru di SDN 001 dan 003 Palaran - Abriani Setya Adisty; Dwi Hendriani; Nino Adib Chifdillah; Badar Badar (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
Stress due to work can be said to be a main issue experienced by elementary school teachers due to job demands, administrative burdens, and additional responsibilities outside of teaching activities, which can negatively impact their mental health, performance, and the quality of learning. Therefore, effective work-related stress management is needed through health education using innovative and engaging media, one of which is the Genially website-based gamification platform. This study is intended to analyze the impacts of health education utilizing the Genially web-based gamification platform on the levels and management of work-related stress among teachers at SDN 001 and SDN 003 Palaran. This study employs a pre-experimental design with a one-group pretest–posttest approach. The study sample consists of all teachers at SDN 001 and SDN 003 Palaran, selected using total sampling. Data collection was completed before and after the intervention using the Perceived Stress Scale (PSS-10) questionnaire to measure work stress levels and the Brief COPE questionnaire to measure work stress management. Data were analyzed using the Wilcoxon test. The findings proved a significant difference in teachers’ work stress levels and work stress management before and after receiving health education using the Genially website-based gamification platform. The intervention was able to reduce work stress levels and improve teachers’ ability to manage work stress.